“Hope” in Nada Jarrar’s an Unsafe Haven: Sisyphean and Cruel - Abdel Khaleq, A’yah Naim; Salman, Dina (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims at examining the portrayal of hope through the lens of Affect theory. The objective of this study is to examine the way that hope motivates the characters of the novel to behave. The study also aims at examining how hope as an emotion does not bring about an optimistic outlook in the world of the novel, but rather creates disillusionment and pessimism. Methods: This paper relies on affect theory particularly the works of Sara Ahmad’s “happy objects” and Lauren Berlant’s concept of “cruel optimism” in showing how hope in Jarrar’s novel is both an object of happiness and a source of misery for the characters of the novel. Results: These results of this study show that studying the notion of hope that the characters seek in concepts and ideas such as marriage, love, and revolutions leads to what we would like to call a “Sisyphean” hope that further leads to disillusionment and discouragement. This hope we argue is not only “Sisyphean,” it is “cruel” because it is both futile and unattainable. Conclusion: We conclude that the effect of hope is concurrently a source of optimism for a better future and Sisyphean in its cruelty as it leads to nothing but agony.